Preferential Gifts in Islamic Law: A Critical Analysis of Hiba Tafzili and Its Impact on Women’s Right to Inheritance in Pakistan - Mr. Shahir Hadi,; Dr. Muhammad Akbar Khan, (Al-Amīr Research Journal for Islamic Studies, 2024)
This research paper critically evaluates the notion of Hiba Tafzili, or preferential gift, in the domain of Islamic law and its consequences on women's right to inheritance within the domain of Pakistani law. It explores the basic Islamic values like fairness, justice, etc., together with the respect of rights of men and women versed particularly in inheritance. While this is the teaching of Islam, the general view is that Hiba Tafzili is used as a tool for the alienation of women from their ancestral properties and that it really is a notion and practice that promotes economic injustice. The paper discourses exactly on the concepts and categories of Hiba with divergent views of many jurists regarding the meaning of Hiba on behalf of one heir rather than the others. The pertinent case laws from both Pakistan courts, which exhibit the dichotomy in judicial interpretation voicing validations regarding the preferential gifts on one side, and nullification on the other, underscore the tension between legal permissibility and moral considerations. It appeals for a new legal position about Hiba Tafzili within Pakistan, which in turn would serve the interest of women and equitable distribution of property requirements based on the spirit of Islamic law, as well as recommend changes consistent with fairer interpretations of Islamic law than those that currently exist. Keywords: Preferential Gifts, Hiba Tafzili, Women’s Right to Inheritance, Legal System of Pakistan